B. Abortus Modulates Osteoblast Function Through the Induction of Autophagy - Pesce Viglietti, Ayelén Ivana; Gentilini, Maria Virginia; Arriola Benitez, Paula Constanza; Giambartolomei, Guillermo Hernán; Delpino, María Victoria (Frontiers in Cellular and Infection Microbiology, 2018)
Osteoarticular brucellosis is the most common localization of human active disease. Osteoblasts are specialized mesenchymal-derived cells involved in bone formation and are considered as professional mineralizing cells. Autophagy has been involved in osteoblast metabolism. The present study demonstrates that Brucella abortus infection induces the activation of the autophagic pathway in osteoblast cells. Autophagy was revealed by upregulation of LC3II/LC3I ratio and Beclin-1 expression as well as inhibition of p62 expression in infected cells. Induction of autophagy was also corroborated by using the pharmacological inhibitors wortmannin, a PI 3-kinase inhibitor, and leupeptin plus E64 (inhibitors of lysosomal proteases). Autophagy induction create a microenvironment that modifies osteoblast metabolism by the inhibition of the deposition of organic and mineral matrix, the induction of matrix metalloproteinase (MMP)-2, osteopontin and RANKL secretion leading to bone loss. Accordingly, autophagy is also involved in the down-modulation of the master transcription factor in bone formation osterix during B. abortus infection. Taking together our results indicate that B. abortus induces the activation of autophagy pathway in osteoblast cells and this activation is involved in the modulation of osteoblast function and bone formation.